The contemporary approaches in teaching foreign languages. Their main characteristics (Eurasian Journal of Philology Science and Education, 2016)
This article considers the current directions of teaching foreign languages in a higher education system. For this purpose, the methods of teaching foreign languages have become the achievement of professional realization of the individual. This article considers approaches such as personal-oriented, communicative and method of project work in teaching foreign languages and their main characteristics. The personal-oriented teaching, a student’s productive side of leaning process determined by the contemporary concept of language education. This concept of key categories is a language, which is the purpose of education; and language is a tool of socio – cultural activities. The main aspect of this concept is a productive leaning activity of students, oriented to the creation of student’s educational product in a foreign language which determines its content. In modern method of teaching foreign language the main point is to develop communicating skills, to form communicative competence. Among the variety of new teaching technologies, aimed at implementing the student-centered approach in the method of teaching is the project work, which distinguishes cooperative character of fulfilling the task, being creative itself and oriented to the development of personality of learners.
Keywords: personal-centered approach; communicative approach; method of projects; a language is a tool of social-cultural activity; productive learning activities.